Economists and their travels, or the time when JFK sent Douglass North on a mission to Brazil - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2017)
The role of traveling as a source of discovery and development of new ideas has been controversial in the history of economics. Despite their protective attitude toward established theory, economists have traveled widely and gained new insights or asked new questions as a result of their exposition to "other" economic systems, ideas and forms of behavior. That is particularly the case when they travel to new places while their frameworks are in their initial stages or undergoing changes. This essay examines economists' traveling as a potential source of new hypotheses, from the 18th to the 20th centuries, with a detailed case study of Douglass North's 1961 travel to Brazil.
Keywords: B00; B30; B41; 330; Travel; economic theories; Douglass North; Brazil; otherness